The effect of enhanced recovery after surgery on the risk factors of venous thromboembolism for patients with gynecologic malignancies - Xu, Jie; Liu, Shanshan; Liu, Dan; Wang, Yina; Tang, Meilan (Frontiers in Oncology, 2025)
ObjectiveThis study aims to evaluate the efficacy of enhanced recovery after surgery (ERAS) in mitigating the risk of venous thrombosis in patients undergoing surgery for gynecological malignancies.MethodsThis prospective randomized controlled trial enrolled patients from January 2019 to December 2022, who were randomly assigned to either the experimental group (ERAS management) or a control group (conventional treatment). The primary endpoints were perioperative venous thrombosis risk indicators, while secondary outcomes involved the incidence of venous thromboembolism (VTE) events and other clinically relevant adverse events.ResultsA total of 177 patients were included, with 91 in the experimental group and 86 in the control group. Preoperative characteristics were comparable between the groups (P>0.05). At one-week post-surgery, the experimental group exhibited higher hemoglobin levels and lower white blood cell counts, D-dimer values, and proportions of patients classified as high risk for thrombosis compared to the control group (P<0.05). Additionally, the incidence of VTE events was significantly lower in the experimental group one month post-surgery (P<0.05).ConclusionThe implementation of ERAS significantly reduces perioperative venous thrombosis risk in patients with gynecological malignancies, demonstrating both safe and effective.